FACTORS ASSOCIATED WITH NUTRITIONAL STATUS OF PREGNANT WOMEN IN PAAL V HEALTH CENTER OF JAMBI CITY, 2018 - Ika Murtiyarini; Enny Susilawati (Poltekkes Kemenkes Jambi, 2018)
The main causes of lack of food, especially for children and mothers, are poverty, no food, recurrent illness, inappropriate feeding practices and lack of care and hygiene. Nutritional problems that are often found in pregnant women are iron nutritional anemia, obesity or overweight, diabetes mellitus, and hypertension. The prevalence of pregnant women with chronic energy deficiency (KEK) in Indonesia is 21.6%, and the infant mortality rate in Indonesia in 2012 was 32 per 1,000 live births. Analytical research with cross sectional approach to determine factors related to nutritional status of pregnant women in Paal V Health Center Jambi City in 2018. The population in this study were all pregnant women who visited Paal V Health Center in Jambi City, amounting to 50 people. Samples were taken by accidental sampling technique so that 50 pregnant women were obtained. The study was conducted at Paal V Public Health Center in Jambi City in August 2018. Data analysis wasunivariate and bivariate. The results showed that a small proportion (20%) of pregnant women experienced poor nutritional status, a small proportion (24%) of pregnant women with low economic status, found that most (82%) of pregnant women had a good medical history, a small proportion (22%) were obtained. pregnant women giving daily food is not good, most of them (96%) pregnant women experience good personal hygiene. The results of data analysis showed that there was a significant relationship between economic status and nutritional status of pregnant women (p-value = 0.007), there was no significant relationship between health history and nutritional status of pregnant women (p value = 0.435), there was a relationship between daily food provision with nutritional status of pregnant women (p-value = 0.006), and there was no significant relationship between personal hygiene and nutritional status of pregnant women (p-value = 0.562). It is expected that this research can be used as input and additional information in seeking to improve the nutritional status of pregnant women, especially to prevent the occurrence of SEZ in pregnant women.